A comprehensive review on source, types, effects, nanotechnology, detection, and therapeutic management of reactive carbonyl species associated with various chronic diseases - Shivkanya Fuloria; Vetriselvan Subramaniyan; Sundram Karupiah; Usha Kumari; Kathiresan Sathasivam; Dhanalekshmi Unnikrishnan Meenakshi; Yuan, Seng Wu; Rhanye Mac Guad; Kaviraja Udupa; Neeraj Kumar Fuloria (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
Continuous oxidation of carbohydrates, lipids, and amino acids generate extremely reactive carbonyl species (RCS). Human body comprises some important RCS namely hexanal, acrolein, 4-hydroxy-2-nonenal, methylglyoxal, malondialdehyde, isolevuglandins, and 4-oxo-2- nonenal etc. These RCS damage important cellular components including proteins, nucleic acids, and lipids, which manifests cytotoxicity, mutagenicity, multitude of adducts and crosslinks that are connected to ageing and various chronic diseases like inflammatory disease, atherosclerosis, cerebral ischemia, diabetes, cancer, neurodegenerative diseases and cardiovascular disease. The constant prevalence of RCS in living cells suggests their importance in signal transduction and gene expression. Extensive knowledge of RCS properties, metabolism and relation with metabolic diseases would assist in development of effective approach to prevent numerous chronic diseases. Treatment approaches for RCS associated diseases involve endogenous RCS metabolizers, carbonyl metabolizing enzyme inducers, and RCS scavengers. Limited bioavailability and bio efficacy of RCS sequesters suggest importance of nanoparticles and nanocarriers. Identification of RCS and screening of compounds ability to sequester RCS employ several bioassays and analytical techniques. Present review describes in-depth study of RCS sources, types, properties, identification techniques, therapeutic approaches, nanocarriers, and their role in various diseases. This study will give an idea for therapeutic development to combat the RCS associated chronic diseases.